A robust design of the forming process parameters of the metallic bipolar plate for proton exchange membrane fuel cells. (15th December 2022) - Yang, Haodi; Jiang, Tianhao; Xu, Zhutian; Peng, Linfa
Abstract: Metallic bipolar plates are important components of the proton exchange membrane fuel cell. To achieve higher performance of fuel cells, dozens of fine flow channels with the width of approximately 1 mm and a high aspect ratio of over 0.3 are required for bipolar plates. Those functional demands push the forming process of bipolar plates to the limit of material and tools, making the rupture sensitive to even a tiny deviation of the tools' geometric dimensions and material properties. To address that, a robust design method is established in this work to analyze the rupture probability by introducing the stochastic variation of material properties and tools' geometric dimensions. Utilizing the method, the rupture probability is decreased from 19.14% to 0.18% during the practical forming of metallic bipolar plates by parameters control. The yield rate is also verified to be over 99.5%. Graphical abstract: Image 1 Highlights: A robust design method is established for forming metallic bipolar plates. The stochastic deviation of material properties and tool dimensions are considered. Criteria of those factors are provided for the fracture-free stamping process design. High-quality metallic bipolar plates are fabricated with a yield rate of over 99.5%.